Criminal Justice of Children as Perpetrators of Abortus Provocatus Criminalis Due to Promiscuity - Saputri, Adhalia Septia (Indonesian Journal of Multidisciplinary Science, 2023)
The child protection system and criminal justice system in Indonesia face significant issues, including a lack of coordination and recognition of unique considerations for juveniles who commit sexual offenses. Children who become victims of sexual crimes that cause pregnancy are often subjected to abortion, which can be abortus provocatus criminalis, which occurs due to illegal actions or not based on medical indications. This research used a qualitative method and a stand-alone qualitative research design to analyze data related to the criminal justice of children as perpetrators of abortus provocatus criminalis due to promiscuity. The Juvenile Criminal Justice System in Indonesia includes criminal investigation and prosecution, juvenile trials, and coaching, guidance, supervision, and assistance during and after committing crimes. Law Number 11 of 2012 mandates diversion at the level of investigation, prosecution, and examination of child cases in the district court, but only for crimes threatened with imprisonment under 7 years and not repetition of crimes.